STRATEGIC IMPERATIVES OF MANAGING CHANGE IN NIGERIAN FINANCIAL INSTITUTIONS - Fatai Alani, Lawal; Akeem, Taiwo; Edwin M., Agwu,; Omotayo A., Adegbuyi, (IJRDO - Journal of Business Management, 2016)
In recent times, there have been changes within the Nigeria financial institutions due to globalisation and technological innovations. While the changes are expected to bring about transformation of the industry in line with global best practices, the attendant effects of strategic alliances between financial institutions and re-structuring exercises occasioned by various banking reforms have brought about untold hardship unto the bank employees. With emerging entities embarking on downsizing of workforce as a cost cutting management strategy, the victims (individuals) who have lost their jobs have to grapple with the need to cope with life, the survivors (staff who survived the downsizing exercise) have to battle with the challenges of work place, while the organisation (executioner of change) have to contend with managing the resistance to change. Successful management of change is therefore crucial to any organization to survive in the present highly competitive and continuously evolving business environment. In order to understand why some change implementations succeed and some fail, how the resistance to those changes work and where it comes from becomes imperative. The study reviewed facets of change and situated resistance to change within the context of Nigerian financial institutions based on secondary data and information. It identifies amongst others, clear and unambiguous objective setting, effective communication, consultation, dialoguing and bargaining, motivation, negotiation, manipulation, co-option and coercion as possible tactics for managing resistance. Managers should take cognisance of the human elements in coping with challenges of change through sustained flexibility and daptability to consequences of change.